Suppression to Visual, Auditory, and Gustatory Stimuli Habituates Normally in Rats With Excitotoxic Lesions of the Perirhinal Cortex. - Robinson, Jasper; Sanderson, David J.; Aggleton, John P. (Behavioral Neuroscience, 2009)
In 3 habituation experiments, rats with excitotoxic lesions of the perirhinal cortex were found to be indistinguishable from control rats. Two of the habituation experiments examined the habituation of suppression of responding on an appetitive, instrumental baseline. One of those experiments used stimuli selected from the visual modality (lights), the other used auditory stimuli. The third experiment examined habituation of suppression of novel-flavored water consumption. In contrast to the null results on the habituation experiments, the perirhinal lesions disrupted transfer performance on a configurai, visual discrimination, indicating the behavioral effectiveness of the lesions. Implications for comparator theories of habituation are considered, and it is concluded that others' demonstrations of the sensitivity of object recognition to perirhinal cortex damage is not the result of standard habituation. Reprinted by permission of the publisher.